The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1200/jco.2014.32.3_suppl.383
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiation (CRT) followed by surgery and adjuvant capecitabine plus oxaliplatin (CAPOX) compared with induction CAPOX followed by concomitant CRT and surgery for locally advanced rectal cancer: Results of the Spanish GCR-3 randomized phase II trial after a median follow-up of 5 years.

Abstract: 383 Background: In locally advanced rectal cancer in contrast with the conventional approach the administration of chemotherapy prior to chemoradiation (CRT) and surgery allow most patients receive planned treatment with better toxicity profile without compromising the pCR and complete resection rates, as we previously demonstrated. (J Clin Oncol 28:859-865, 2010). We now report on the 5-year outcomes of this randomized trial. Methods: Patients with distal or middle third, T3-T4 and/or N+ rectal adenocarcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…We have thus demonstrated that this novel regimen of split-course CRT with concurrent oxaliplatin–5-FU and FOLFOX chemotherapy in the RT-free window is tolerable, deliverable and has demonstrated promising structural and functional imaging response rates for both primary and metastatic disease. There are several ways of optimising the regimen further to increase the control of the systemic disease while maintaining local control, including the utility of initial induction chemotherapy prior to CRT ( Shin et al , 2011 ; Cercek et al , 2013 ; Fernandez-Martos et al , 2014 ), the utility of an irinotecan-5-FU backbone ( Glynne-Jones et al , 2007 ; Nakamura et al , 2014 ), or biological agents ( Crane et al , 2010 ; Gasparini et al , 2012 ; van Dijk et al , 2013 ). The regimen reported here is now being evaluated with the addition of bevacizumab and in patients with locally advanced disease without metastases (TROG 0901).…”
Section: Discussionmentioning
confidence: 99%
“…We have thus demonstrated that this novel regimen of split-course CRT with concurrent oxaliplatin–5-FU and FOLFOX chemotherapy in the RT-free window is tolerable, deliverable and has demonstrated promising structural and functional imaging response rates for both primary and metastatic disease. There are several ways of optimising the regimen further to increase the control of the systemic disease while maintaining local control, including the utility of initial induction chemotherapy prior to CRT ( Shin et al , 2011 ; Cercek et al , 2013 ; Fernandez-Martos et al , 2014 ), the utility of an irinotecan-5-FU backbone ( Glynne-Jones et al , 2007 ; Nakamura et al , 2014 ), or biological agents ( Crane et al , 2010 ; Gasparini et al , 2012 ; van Dijk et al , 2013 ). The regimen reported here is now being evaluated with the addition of bevacizumab and in patients with locally advanced disease without metastases (TROG 0901).…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant chemotherapy. Capecitabine was taken orally twice daily during the first 9 weeks (days 1-14, 22-35, [43][44][45][46][47][48][49][50][51][52][53][54][55][56]. Oxaliplatin and bevacizumab were administered intravenous for 3 cycles (days 1, 22, 43).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that this new approach leads to prolonged DFS and OS, but phase III trials are currently lacking. Several phase II studies evaluated the role of neoadjuvant chemotherapy with Xeloda ® (capecitabine) and oxaliplatin (CAPOX) or oxaliplatin + 5-fluorouracil (FOLFOX) followed by chemoradiation and surgical resection (19, [45][46][47][48][49][50]. This approach achieved pCR rates of 14-29%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from recent investigations suggests that neoadjuvant CTX has the potential to optimize compliance without compromising a patient's ability to undergo planned CRT or increase the risk of surgical complications (Table 2). 43,[56][57][58][59][60][61][62][63][64] A pooled analysis of the phase II trials, EXPERT and EXPERT-C, published outcomes of 269 patients with MRI-defined high-risk tumors who received oxaliplatin-based neoadjuvant CTX and sequential CRT. The experimental arm was associated with an acceptable toxicity profile and established excellent compliance rates of both NA-CTX (91%) and CRT (88%), with adequate objective radiographic tumor responses, 62% and 80% after each modality, respectively.…”
Section: Total Neoadjuvant Therapymentioning
confidence: 99%